The “whiteness” of the “committal” process within Brazilian mental health policy - Henriques, Cibele da Silva (Argumentum, 2023)
This article analyses the structure of the “whiteness” of the “committal” process within mental healthcare for the black population within Brazilian society, identifying the conflicts and correlations of forces. Qualitative research was conducted, through bibliographical and documental investigation. There are evident contradictions within the construction of Brazilian Psychiatric Reform (BPR). The continuance of a committal based, hospital-centric, and racist culture throughout the structure of the Psychosocial Care Network (Rede de Atenção Psicossocial  - RAPS) were clear, resulting in a link between “whiteness” and management positions, the “whiteness” of the “committal” process within clinical care, the commodification of deinstitutionalisation, and in the criminalisation of harm reduction through the financing of therapeutic communities.